Analisis CAPM Dalam Pembentukan Portofolio Optimal Pada Jakarta Islamic Indeks Saat Resesi Di Indonesia - Kurniawan, M. Arif; Suci, Rafita Vani Eka (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2021)
The purpose of this study is to determine the optimal portfolio formation usingcapital asset pricing model analysis, besides that this study also calculates theproportion of funds in each company's stock and calculates the amount of realizedreturn and expected return as well as portfolio risk. The research design usedquantitative descriptive analysis. The population of this research is stocks that areincluded in the Jakarta Islamic Index (JII) during the recession in Indonesia,namely November 20, 2020 to May 31, 2021. By using the purposive samplingmethod in determining the sample criteria and obtained a number of 29 companiesas research samples. The method in forming the optimal portfolio uses the capitalasset pricing model. The results of the research are 29 companies that fall into theoptimal stock category, there are 12 companies including MDKA, JPFA, ANTM,TKIM, SCMA, EXCL, UNTR, AKRA, MNCN, CPIN, TLKM, PTPP and other sharesthere are 17 stocks that are not included in optimal stock category. Calculationsusing the CAPM method obtained a CAPM value of 0.01708 which means that thevalue of the rate of return on an asset in a company incorporated in the JakartaIslamic Index for the research period is 0.01708 with a market variance of 0.00062and a portfolio variance of 1.13500.